A ROUGH MOTORIC MODULE FOR KINDERGARTEN TEACHERS: RESEARCH AND DEVELOPMENT - Sunarsih Sunarsih; Rufi’i Rufi’i; Djoko Adi Walujo (JURNAL PAJAR (Pendidikan dan Pengajaran), 2021)
The aim of this development was to produce a rough motoric module for early childhood Education (PAUD). This research was included as research and development (R&D) with Brog and Gall model which consists of seven stages. The result of validation from material experts obtained that the average percentage of the feasibility of the modules was 93% (very feasible). Then, the result of validation from design experts obtained a percentage of 90% (very feasible); the result of small group assessments by subject teachers was 97% (very feasible;) and the result of large group test by all teachers in group III was 96% (very feasible). The module provided an open opportunity for PAUD teachers to develop children's rough motoric skills. Moreover, rough motoric development materials provided a variety of new learning styles so they enriched insights to PAUD teachers. It could be concluded that the module was suitable to be used by kindergarten teachers. This module could also be used as a reference for teachers in PAUD educational institutions.